Working of Buko (The Modern Long Distance Crane in Kulu Forest Division), Punjab - Nibajan Singh, S. (Indian Forester, 1958)
This paper deals with problems or timber extraction in high hills of Kulu Forest Division. Efforts have been made to introduce mechanical means of logging in this area. Details of installation and working of Buko SkyLine Crane have been given. It is not possible yet to draw any final conclusion as the working has been rather limited but valuable experience gained in this connection has been narrated.